2015
DOI: 10.4014/jmb.1505.05035
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Co-Expression of Phytoene Synthase Gene from Kocuria gwangalliensis in Escherichia coli

Abstract: A phytoene synthase gene, crtB, was isolated from Kocuria gwangalliensis. The crtB with 1,092 bp full-length has a coding sequence of 948 bp and encodes a 316-amino-acids protein. The deduced amino acid sequence showed a 70.9% identity with a putative phytoene synthase from K. rhizophila. An expression plasmid, pCcrtB, containing the crtB gene was constructed, and E. coli cells containing this plasmid produced the recombinant protein of approximately 34 kDa , corresponding to the molecular mass of phytoene syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…However, due to the absence of phytoene biosynthetic genes, studying carotenoid biosynthesis in E. coli requires extension of the general terpenoid pathway with CrtB and CrtE for the production of phytoene, which is a precursor of carotenoids (Seo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the absence of phytoene biosynthetic genes, studying carotenoid biosynthesis in E. coli requires extension of the general terpenoid pathway with CrtB and CrtE for the production of phytoene, which is a precursor of carotenoids (Seo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…71 PSY requires Mn 2+ as a cofactor to catalyze the condensation of two molecules of GGPP to produce phytoene. 73 In bacteria, PSY is encoded by the crtB gene, while in fungi, PSY is a bifunctional enzyme encoded by the bifunctional gene carRA/ carRP/crtYB, with the activities of phytoene synthase and lycopene cyclase. 74−76 The enzyme first acts as phytoene synthase catalyzing the formation of phytoene from GGPP, and then as a lycopene cyclase, it catalyzes the cyclization of radiodurans R1, and the results showed that the overexpression of crtB was the most effective, with a lycopene titer of 29.9 mg/ L, which was 3.7 times higher than in the control strain.…”
Section: Key Enzymes In the Downstreammentioning
confidence: 99%